The First Dime: A Decade of Convict Criminology - Murphy, Daniel S. (2009)
This article discusses the historical origins of Convict Criminology (CC); intellectual legacy of CC; organization of the CC group; allies in the CC struggle; recent activities of the CC group; impact of CC on the study of jails, prisons, and community corrections; and the authors' future plans. Thus, the focus of this article is on taking stock of the development of CC and identifying the accomplishments to date